Origin tracing of coffee beans in Region XII of the Philippines through multi-element and stable isotope profiling using pXRF and IRMS - Dela Fuente, Danielle N. (Animo Repository, 2023)
Coffee is one of the most popularly consumed beverages by numerous individuals daily. Recent trends show that there is an increasing interest in sourcing based on its geological location such as those seen in single-origin produced coffee beans. This study identified the multi-elemental fingerprints and stable-isotope profile of coffee beans coming from Region XII of the Philippines using a portable ED-XRF (pXRF) and Isotope Ratio Mass Spectrometry (IRMS). Coffee bean samples were received from Philippine farms originating in Sarangani, North Cotabato, South Cotabato, and Sultan Kudarat. Unroasted beans were oven-dried for 24 hours at 60°C followed by grounding and pulverization. Once the samples have a powder consistency, they are formed into a pellet before analysis via pXRF. The sieved coffee grounds were subjected to IRMS analysis to obtain its stable isotope ratios for carbon and nitrogen. The multi-element and stable isotope profiles are processed by Random Forest to classify findings by geographical location and variety of coffee. With pXRF and IRMS, it was found that K, Mg, Al, P, S, Si, Cl, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, As, Se, Rb, Sr, Y, Zr, Nb, Mo, Rh, Pd, Ag, Cd, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pt, Au, Hg, Tl, Pb, Bi, Th, U, N, δ15N, C, and δ13C were detected. This study can aid in establishing highly accurate standards for traceability of coffee beans, thus improving the authenticity of Philippine coffee.